1994
DOI: 10.1177/001872089403600213
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Fatigue of C-141 Aircrews during Operation Desert Storm

Abstract: Airlift crews were exposed to extended work periods, reduced sleep periods, night work, and circadian dysrhythmia caused by shift work and time-zone crossings during Operations Desert Shield and Desert Storm. This research reveals the extent to which severe subjective fatigue was experienced by the crews during Operation Desert Storm. In addition, through the evaluation of long-term and short-term work and sleep histories, this research shows that recent sleep and flight histories are correlated with high fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 17 publications
3
15
0
1
Order By: Relevance
“…Earlier studies mainly tested verbal performance and articulation and found them to be negatively impacted by sleep deprivation (Harrison & Horne, 1998;Neville, Bison, French, & Boll, 1994;Schein, 1957). These findings are also supported by more recent studies (Bagnall, Dorrian, & Fletcher, 2011;Krajewski, Batliner, & Golz, 2009;Liu & Wissow, 2011;Orzeł-Gryglewska, 2010).…”
Section: Introductionsupporting
confidence: 60%
“…Earlier studies mainly tested verbal performance and articulation and found them to be negatively impacted by sleep deprivation (Harrison & Horne, 1998;Neville, Bison, French, & Boll, 1994;Schein, 1957). These findings are also supported by more recent studies (Bagnall, Dorrian, & Fletcher, 2011;Krajewski, Batliner, & Golz, 2009;Liu & Wissow, 2011;Orzeł-Gryglewska, 2010).…”
Section: Introductionsupporting
confidence: 60%
“…For example, the mean percentage change in RMSE was 4.8% from the five early to the five late flights, but two pilots showed changes of greater than 30% and three pilots actually showed improvements in flight performance from the early to later flights. The existence of individual differences in "fatigue resistance" has long been noted in the literature and has been attributed mostly to recent sleep history (Caldwell et al, 2005;Neville, Bisson, French, Boll, & Storm, 1994), baseline arousal (Caldwell et al, 2005), or personality factors such as introversion that may be linked to higher levels of baseline arousal (May & Kline, 1987;Smith & Mabien, 1993). Although we did not observe any correlation between flight performance decrements and recent sleep history as measured by FAST, it should be stressed that the data concerning sleep length and quality that we entered into the FAST model were based on pilots' self-reports and not on objective measures.…”
Section: Discussionmentioning
confidence: 99%
“…U.S. Air Force F-15 pilots in Operation Desert Storm indicated that around-the-clock task demands, minimal rest periods, consecutive duty days, circadian disruptions, and sleep deprivation were commonplace ( 58 ), as did F-16 pilots ( 189 , 190 ). U.S. Air Force C-141 pilots in Operation Desert Storm likewise complained that insuffi cient sleep and lengthy fl ight times were primarily responsible for increased fatigue ( 147 ).…”
mentioning
confidence: 99%